1987
DOI: 10.1300/j082v14n01_17
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy with Gay/Lesbian Couples and Their Children in "Stepfamilies":

Abstract: As increasing numbers of gay/lesbian parents and their children enter into "stepfamily-like" relationships with a gay partner, they are beginning to seek therapy for difficulties peculiar to stepfamily living involving two same-sex partners. This paper focuses on the difficulties experienced by gay parents and children in a step-relationship, and seeks to sensitize mental health professionals to issues specific to intervention with such families. Effective therapy with these families requires that therapists b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Kurdek (1988) suggested that lesbian relationships are not necessarily better than gay relationships, rather that higher scores for lesbians may be due to socialization which reinforces nurturance, expressiveness, and caring among females. Baptiste (1987) used the term "stepfamily" to denote a cohabitative living arrangement which includes two adults and their children-biological, adopted, or conceived through alternative insemination from previous heterosexual relationships. The family science literature rarely identifies as stepfamilies two same-sex adults who live together and raise children who were conceived in previous heterosexual relationships.…”
Section: Characteristics Of Lesbian Couplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Kurdek (1988) suggested that lesbian relationships are not necessarily better than gay relationships, rather that higher scores for lesbians may be due to socialization which reinforces nurturance, expressiveness, and caring among females. Baptiste (1987) used the term "stepfamily" to denote a cohabitative living arrangement which includes two adults and their children-biological, adopted, or conceived through alternative insemination from previous heterosexual relationships. The family science literature rarely identifies as stepfamilies two same-sex adults who live together and raise children who were conceived in previous heterosexual relationships.…”
Section: Characteristics Of Lesbian Couplesmentioning
confidence: 99%
“…The family science literature rarely identifies as stepfamilies two same-sex adults who live together and raise children who were conceived in previous heterosexual relationships. However, these same-sex relationships are characterized by mutual commitment, property sharing, emotional and physical intimacies similar to cohabiting heterosexual couples with children (Baptiste, 1987). Still, the family science and family therapy literature has all but ignored them, including the unique challenges they face and their possible similarity with the growing number of heterosexual stepfamilies.…”
Section: Characteristics Of Lesbian Couplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesbian mothers and their families have been shown to benefit from family therapy where changes in the family structure can be discussed (Kirkpatrick et al, 1981;Kirkpatrick, 1987), or where factors affecting families with gay step-parents can be addressed (Baptiste, 1987). There are also suggestions that adolescents who have a gay or lesbian parent may sometimes benefit from therapeutic intervention (Ross, 1988), if they have difficulties in forming a stable sexual identity.…”
Section: The Gay or Lesbian Parentmentioning
confidence: 99%
“…Lesbian/gay-parented families remain underrepresented, largely ignored, and even presented as deviant in education (Byard et al 2013;Casper, Schultz & Wickens 1992). Further, children often experience rejection, bullying, or discrimination from their peers (Baptiste Jr 1987;Breshears 2011;Butler, Alpaslan, Strümpher & Astbury 2003;Gartrell, Deck, Rodas, Peyser & Banks 2005;Lewis 1980). In perhaps the largest study of school experiences in the United States, including surveys from 588 lesbian and gay parents and 154 children, Kosciw and Diaz (2008) found that many children reported being mistreated at school for having a lesbian or gay parent, with 40% reporting verbal harassment because of their families.…”
Section: Introductionmentioning
confidence: 99%